Not a care in the world: an exploration of the personal–professional–political nexus of international development practitioners working in security and justice sector reform. Issue 5 (20th October 2021) - Jones, Briony; Gordon, Eleanor
ABSTRACT: This article explores the implications for international development policy and practice (specifically within security and justice sector reform) of the departure of those assuming caring roles, predominantly women who become mothers. More broadly, the article investigates how personal life stories impact the choices that we make in our professional lives, including where, when, and how we engage, in this instance, in international development, and the subsequent implications for the field. These choices (the personal) have an impact on policy and practice (the professional) and inform how knowledge is created, circulated, legitimized, and becomes expert knowledge (the political). This article thus explores the implications of an epistemic community being predominantly male (in part as a consequence of the lack of support for social reproductive work) for how security and justice in post-conflict environments are conceived and, ultimately, rebuilt. We reflect on our own engagement in such environments – as scholars and former practitioners – and draw on the life stories of international development practitioners to investigate the personal–professional–political nexus and the impact of narrow epistemic communities on how "security work" is done, whose security matters, and whose voices count.